Criminal Justice Implications of Bankruptcy Abuse Against Solvent Debtors - Hairul Rizal H Talib; Ahmad Dwi Nuryanto; Maya Khater (Jurnal Justice Dialectical, 2026)
Bankruptcy law provides a legal mechanism for resolving financial distress while safeguarding the legitimate interests of creditors and debtors. However, creditors may misuse bankruptcy proceedings against solvent debtors and transform a legitimate debt recovery mechanism into a means of coercion, procedural manipulation, and economic pressure. This practice raises serious criminal justice concerns when parties deliberately present misleading claims, conceal material financial information, manipulate judicial procedures, or initiate bankruptcy proceedings to pressure debtors who retain sufficient financial capacity to meet their obligations. This study examines the criminal justice implications of bankruptcy abuse against solvent debtors and evaluates whether the existing legal framework provides adequate safeguards against the misuse of bankruptcy proceedings. The research applies normative legal research through statutory, conceptual, and comparative approaches. The findings reveal that the current bankruptcy framework primarily determines bankruptcy through formal requirements concerning the existence of multiple creditors and at least one due and payable debt. Courts therefore may declare a debtor bankrupt without first determining whether the debtor actually lacks the financial capacity to satisfy its obligations. This legal structure exposes solvent debtors to bankruptcy petitions even when they possess sufficient assets and maintain viable business operations. More importantly, the absence of a substantive insolvency assessment enables parties to exploit bankruptcy proceedings for objectives unrelated to legitimate debt recovery. Fraud, deception, coercion, and deliberate procedural manipulation in bankruptcy proceedings may undermine procedural fairness, disrupt business continuity, and weaken the integrity of judicial institutions. Comparative analysis shows that an insolvency test can establish a substantive safeguard against abusive bankruptcy petitions by requiring an objective assessment of the debtor’s financial condition. This study therefore proposes the incorporation of an insolvency test alongside stronger legal mechanisms for detecting and addressing abusive conduct in bankruptcy proceedings. These reforms would strengthen protection for solvent debtors, prevent procedural manipulation, reinforce legal accountability, and advance substantive justice within the criminal justice system.